Evaluation of Methyl Eugenol Doses against Bactrocera zonata S. (Diptera: Tephritidae) in Ber fruit Orchard in Bahawalpur, Pakistan - Bakhs, Allah; Hassan, Muhammad Waqar; Maqsood, Sohail; Sarwar, Ghulam (BioScientific Review, 2022)
Among the fruit flies, Bactrocera zonata S. (Diptera: Tephritidae) is native to South and Southeast Asia. It is commonly found in India and Pakistan but it is also found in more than 20 countries in Asian and African regions. In this study, fruit fly male annihilation traps containing different doses of methyl eugenol (ME) attractant, ranging from 0.1, 0.2, 0.3, 0.4, 0.5, 0.75, 1.0 ml dose, and a control treatment (water only) were analyzed. Additionally, a uniform application of one milligram of toxicant Trichlorfon applied in all traps was installed in a Ber orchard in Bahawalpur, Pakistan. The prime purpose of this study was to evaluate the relative efficacy of ME doses against B. zonata in this region. Apart from this, knowledge of seasonal population change could help in controlling these pest insects. Therefore, experiment data for the population was recorded on fortnightly basis from Feb 7, 2018-April 04, 2018 and onward on a weekly basis till May16, 2021 after which the population started to decline. No fruit fly adults were attracted to traps containing water only during all observed dates. Maximum population of B. zonata on Feb 7, 2018, was 3 at ME concentrations of 0.2 ml, 0.75 ml, and 1.0 ml, on Feb 21, 2018, its population was 0.667 at 0.2 ml concentration, on March 07, 2018 the population was 14.667 at 1.0 ml concentration, on March 21, 2018, the population was 3.667 at 0.5 ml concentration, on April 04, 2018, the population was 60.333, on April 11, 2018, the population was 69.000 at 1.0 ml concentration, on April 18, 2018, the population was 94.667 at 0.5ml concentration, on April 26, 2018, the population was 400.670, on May 02,2018, the population was 247.333, on May 9, 2018, the population was 181.667, and on May16, 2018, population was 20.667 at 1.0 ml concentration of methyl eugenol. Thus, more concentrations of ME usually attracted more flies. B. zonata population remained low in February and March. In April the population started to build up and reached its peak at the end of April. In May, the population started to decrease and it declined after mid-May. Correlation with weather factors showed that temperature had a positive while relative humidity showed a negative effect on B. zonata population. This above collected data gave useful information about the population dynamics of fruit flies in the Asian region and an effective attractant dose for the better management of these fruit flies.